Interaction of Socioeconomic Status with Risky Internet Use, Gambling and Substance Use in Adolescents from a Structurally Disadvantaged Region in Central Europe - Petruzelka, Benjamin; Vacek, Jaroslav; Gavurova, Beata; Kubak, Matus; Gabrhelik, Roman; Rogalewicz, Vladimir; Bartak, Miroslav (International journal of environmental research and public health, 2020)
BACKGROUND AND AIMS: The current level of knowledge concerning the effect of socioeconomic status (SES) on internet use, gambling, and substance use in structurally disadvantaged regions is scarce. The objective of this study was an investigation of the relationship between SES and risky internet use, gambling and substance use in a structurally disadvantaged region in Central Europe. METHODS: A cross-sectional survey was conducted among high school students (n = 1063) in a Czech structurally disadvantaged region in autumn 2017. Binary Logistic Regression models were applied to data from the modified Excessive Internet Use scale (mEIUS), a standard tool for measuring the risk of addictive behavior on the internet and the risk of excessive gaming. Other data were collected using the Lie/Bet (problematic gambling), CAGE (acronym of the key words: cut, angry, guilty and eye-opener), and the Cannabis Abuse Screening Test (CAST) (problematic alcohol/cannabis use) tools. RESULTS: There were statistically significant differences between at-risk and not-at-risk groups in addictive behavior on the internet and gaming, while none were found in problematic gambling. Individual dimensions of SES showed significant effects on substance use. Regarding parenting styles, significant differences were found only in the risk of addictive behavior on the internet or gaming between the authoritarian and authoritative styles. Being engaged in behavioral addictions with one´s parents increased the odds of the behavioral addiction risk and decreased the odds of the substance addiction risk. Engagement with one´s parents in substance addictions decreased the odds of the behavioral addiction risk and increased the odds of the substance addiction risk. DISCUSSION AND CONCLUSIONS: The results point at specific relations between SES and the risk of addictive behaviors on the internet and gaming within structurally disadvantaged regions. The results of SES and/or structurally disadvantaged region measures obtained in research, policy-making, and care-provision may improve the focus of actions taken.
Keywords: Adolescent; Europe; hráčství; Male; substance use; návykové chování; lidé; Humans; disadvantaged region; socioeconomic status; Evropa; internet; společenská třída; videohry; Vulnerable Populations; Social Class; internet use; Gambling; Video Games; průřezové studie; Substance-Related Disorders; mužské pohlaví; zranitelné populace; adolescents; students; Cross-Sectional Studies; ženské pohlaví; mladiství; Female; poruchy spojené s užíváním psychoaktivních látek; Behavior, Addictive; Internet; gambling